Improved survival after retrieval of 12 or more regional lymph nodes in appendiceal cancer - Fleischmann, Isabelle; Warschkow, René (European journal of surgical oncology, 2017)
Background: To evaluate the role of regional lymph node (RLN) retrieval on stage migration, overall (OS), and cancer-specific survival (CSS) in appendiceal cancer. Methods: Between 2004 and 2012, 1046 patients with primary stage I-III carcinoma of the appendix were identified in the Surveillance, Epidemiology and End Results database. The impact of the number of RLN removed on OS and CSS was assessed using joinpoint regression, Cox regression, and propensity score methods. Results: The rate of node-positive cancer increased with the number of retrieved RLN from 10.5% in patients with one RLN removed to 30.6% in patients with 10 RLNs removed. This leveling off at 10 RLN was confirmed by joinpoint regression analysis (p = 0.023). Despite the finding that retrieval of 10 RLN should be sufficient for appendiceal cancer, for the survival analysis the somewhat higher cutoff of 12 RLN was applied, since this cutoff is recommended by the guidelines for colorectal cancer. Retrieval of 12 or more RLN was beneficial compared to less than 12 RLN retrieved for OS (HR = 0.60, p < 0.001) and CSS (HR = 0.67, p = 0.020) in multivariable analysis, as well as in propensity score matched analysis (OS: HR = 0.58, p = 0.001, CSS: HR = 0.61, p = 0.005). Conclusion: The rate of node-positive cancer increased with the number of retrieved RLN up to about 10 RLN (95%CI: 3.6-16.3, p = 0.023). Over 10 retrieved RLN, the node-positive cancer rate no longer increased. This correlates with the recommended number of 12 RLN to be retrieved in colorectal cancer, but differs from the guideline for neuroendocrine tumors.